Revolutionizing Road Repair: A Comprehensive Review of Innovative Technologies for Pothole Rehabilitation with Waste Plastic - Gagarawa, Abubakar; Adisa, Adewale Oluseye (Journal of Advanced Research in Glass, Leather and Plastic Technology; Vol 6 No 1 (2023): Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
It describes a strategy for repairing roads utilising aggregate and waste plastic garbage. This toxic waste was discovered to make about 9% to 12% of municipal solid waste in various forms. The environmental non-biodegradability of plastic has posed various problems for India's urban and rural areas. Drains clogging, water stagnation, and the emission of harmful gases during open combustion are common issues. The lifespan of historically built roads is less effective, takes a lot longer to create, or requires more manpower. Traditional methods have some flaws.